Corneal Confocal Microscopy Detects Corneal Nerve Damage in Patients Admitted With Acute Ischemic Stroke. Issue 11 (November 2017) - Khan, Adnan; Akhtar, Naveed; Kamran, Saadat; Ponirakis, Georgios; Petropoulos, Ioannis N.; Tunio, Nahel A.; Dargham, Soha R.; Imam, Yahia; Sartaj, Faheem; Parray, Aijaz; Bourke, Paula; Khan, Rabia; et al.
Abstract : Background and Purpose—: Corneal confocal microscopy can identify corneal nerve damage in patients with peripheral and central neurodegeneration. However, the use of corneal confocal microscopy in patients presenting with acute ischemic stroke is unknown. Methods—: One hundred thirty patients (57 without diabetes mellitus [normal glucose tolerance], 32 with impaired glucose tolerance, and 41 with type 2 diabetes mellitus) admitted with acute ischemic stroke, and 28 age-matched healthy control participants underwent corneal confocal microscopy to quantify corneal nerve fiber density, corneal nerve branch density, and corneal nerve fiber length. Results—: There was a significant reduction in corneal nerve fiber density, corneal nerve branch density, and corneal nerve fiber length in stroke patients with normal glucose tolerance ( P <0.001, P <0.001, P <0.001), impaired glucose tolerance ( P =0.004, P <0.001, P =0.002), and type 2 diabetes mellitus ( P <0.001, P <0.001, P <0.001) compared with controls. HbA1c and triglycerides correlated with corneal nerve fiber density ( r =−0.187, P =0.03; r =−0.229 P =0.01), corneal nerve fiber length ( r =−0.228, P =0.009; r =−0.285; P =0.001), and corneal nerve branch density ( r =−0.187, P =0.033; r =−0.229, P =0.01). Multiple linear regression showed no independent associations between corneal nerve fiber density, corneal nerve branch density, and corneal nerve fiber length and relevant risk factors for stroke. Conclusions—: Corneal confocal microscopy is a rapid noninvasive ophthalmic imaging technique that identifies corneal nerve fiber loss in patients with acute ischemic stroke.